Community of Practice (CoP) on climate informed advisory services for livestock farmers: The process of co-development and dissemination in Senegal - Houessionon, Prosper; Worou, Nadine; Chan, Derek; Yessoufou, Adjani Nourou-Dine; Sarr, Mamadou Adama; Konte, Oumar; Sow, Fafa; Wane, Abdrahmane; Whitbread, Anthony M. (2023)
Livestock is an important source of income for millions of smallholder farmers, including women, in Senegal (Habanabakize, Ba, et al., 2022; Habanabakize, Diasse, et al., 2022). But drought, heat waves and extreme wet events, exacerbated by climate change, threaten food security, animal health and the livelihoods of many pastoral communities in the country. With the increased variability of the growing season, natural pasture and water availability, undernourished cattle must travel longer and longer distances.1 In order to reduce uncertainty and to protect their livelihoods and assets, herders utilise various adaptation strategies, including: (1) destocking by selling livestock at often low prices prior to and during to drought; (2) transhumance, which entails a higher risk of animal loss; (3) purchase of feeds which can be costly; (4) utilisation of residues from croplands which may lead to conflict with farmers. In this context, extension services, developed on knowledge and innovations sourced from local- national-international research, can play a vital role in building the capacity of livestock farmers to improve their productivity and profit (Pousga et al., 2022).